Inflated Expectations: How Government Partisanship Shapes Monetary Policy Bureaucrats' Inflation Forecasts. Issue 2 (4th December 2014) - Gandrud, Christopher; Grafström, Cassandra
Abstract : Governments' party identifications can indicate the types of economic policies they are likely to pursue. A common rule of thumb is that left-party governments are expected to pursue policies for lower unemployment, but which may cause inflation. Right-party governments are expected to pursue lower inflation policies. How do these expectations shape the inflation forecasts of monetary policy bureaucrats? If there is a mismatch between the policies, bureaucrats expect governments to implement, and those that they actually do, forecasts will be systematically biased. Using US Federal Reserve Staff's forecasts we test for executive partisan biases. We find that irrespective of actual policy and economic conditions forecasters systematically overestimate future inflation during left-party presidencies and underestimate future inflation during right-party ones. Our findings suggest that partisan heuristics play an important part in monetary policy bureaucrats' inflation expectations.